2014
DOI: 10.1126/science.1255153
|View full text |Cite
|
Sign up to set email alerts
|

Large impacts around a solar-analog star in the era of terrestrial planet formation

Abstract: The final assembly of terrestrial planets occurs via massive collisions, which can launch copious clouds of dust that are warmed by the star and glow in the infrared. We report the real-time detection of a debris-producing impact in the terrestrial planet zone around a 35-million-year-old solar-analog star. We observed a substantial brightening of the debris disk at a wavelength of 3 to 5 micrometers, followed by a decay over a year, with quasi-periodic modulations of the disk flux. The behavior is consistent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 44 publications
3
61
0
Order By: Relevance
“…The vertical dashed lines show the level of variability for sources discussed in Sect. 6.3 Meng et al 2014Meng et al , 2015 we estimate the fraction of Sun-like stars in Upper Sco with detectable 12 µm excesses is ∼ 10 %, in broad agreement with the findings of , particularly if one considers that the fraction is likely to decrease over the 10-120 Myr age range (and noting that some of the Upper Sco excesses are from protoplanetary disks).…”
Section: Photometric Fluxessupporting
confidence: 87%
See 1 more Smart Citation
“…The vertical dashed lines show the level of variability for sources discussed in Sect. 6.3 Meng et al 2014Meng et al , 2015 we estimate the fraction of Sun-like stars in Upper Sco with detectable 12 µm excesses is ∼ 10 %, in broad agreement with the findings of , particularly if one considers that the fraction is likely to decrease over the 10-120 Myr age range (and noting that some of the Upper Sco excesses are from protoplanetary disks).…”
Section: Photometric Fluxessupporting
confidence: 87%
“…Later observations showed that the near-IR (3-5 µm) emission to this star underwent a substantial brightening followed by decay on a year timescale, with quasi-periodic modulations (with period ∼ 30 days) in the disk flux (Meng et al 2014). This was interpreted as the result of a giant collision in which silicate vapour is created out of which small particles condense and subsequently collisionally deplete.…”
Section: Time Variabilitymentioning
confidence: 92%
“…Protoplanetary disks reveal ongoing chemical and spatial processes related to the earliest stages of planet formation, and especially volatile grain chemistry and dust trapping (Pontoppidan et al 2014;van der Marel et al 2016) prior to and possibly during their incorporation into large bodies. Young and mature main-sequence stars reveal systems of fullyfledged planets, their planetesimal belt leftovers, and (giant impact) collisional by-products (Meng et al 2014;MacGregor et al 2017;Chauvin et al 2017). These planetary systems yield final architectures and assemblies, where the physical and chemical processes associated with planet formation are essentially exhausted and thus must be inferred via modeling.…”
Section: Introductionmentioning
confidence: 99%
“…Peculiar light curves and slow trends are common among young stellar objects (YSOs) (Rebull et al 2014;Stauffer et al 2015;Ansdell et al 2016), and may result from the obscuration by dust generated by disintegrating planets (e.g., Rappaport et al 2012Rappaport et al , 2014Sanchis-Ojeda et al 2015) or planetesimal/planet collisions (e.g., Meng et al 2014Meng et al , 2015 if viewed edge-on (Bozhinova et al 2016). However, KIC 8462852 does not appear to fit into either scenario.…”
Section: Introductionmentioning
confidence: 99%